Expression and Purification of -glucuronidase Derived from Bacteria in Doats Rumen from Recombinant Escherichia coli Rosetta (DE3) - Giang, Le Ngoc; Lam, Le Tung; Loan, Tran Thi; Huyen, Do Thi; Hai, Truong Nam (VNU Journal of Science: Natural Sciences and Technology; Vol 34 No 2DO - 10.25073/2588-1140/vnunst.4491, 2018)
α-1,2-Glucuronidase GH67 plays an important role in the degradation of 4-Omethylglucuronic acid ((Me)GlcA) side chain in glucuronoarabinoxylan to enhance lignocellulose converstion into fermentable sugars for production of bioethanol and value-added products from plant biomass. In this study, a gene Gglc1 of 1908 nucleotides coding for mature α-1,2-glucuronidase GH67 derived from bacteria in goats rumen was sucessfully expressed in E. coli Roseta. Most of recombinant enzyme was soluble fraction when the host cultured in TBA, PEA media containing 0.05 mM IPTG at 25oC or 30oC. The recombinant enzyme was purified by His-tag affinity chromatography with purity of 90%. Preliminarily, the enzyme exhibited activity to converse (Me)GlcA present in birchwood xylan into 4-O-methyl-D-glucuronic acid and D-glucuronic acid to reduce pH which was detected by pH indicator bromothymol blue. In future, the recombinant enzyme will be characterized for supplementation into enzyme cocktail for effective lignocellulose conversion into sugar. Keywords -glucuronidase, expression, Escherichia coli, DNA metagenome, Gglc1. References [1] Z. Anwar, M. Gulfraz, M. Irshad, Agro-industrial lignocellulosic biomass a key to unlock the future bio-energy: A brief review, Journal of Radiation Research and Applied Sciences 7 (2014) 163. [2] S. Willför, A. Sundberg, J. Hemming, B. Holmbom, Polysaccharides in some industrially important softwood species, Wood Science and Technology 39 (2005) 245. [3] T.J. Bosmans, A.M. Stépán, G. Toriz, S. Renneckar, E. Karabulut, L. Wågberg, P. Gatenholm, Assembly of debranched xylan from solution and on nanocellulosic surfaces, Biomacromolecules 15 (2014) 924. [4] M.A. Kabel, H. van den Borne, J.-P. Vincken, A.G.J. Voragen, H.A. Schols, Structural differences of xylans affect their interaction with cellulose, Carbohydrate Polymers 69 (2007) 94. [5] Å. Linder, R. Bergman, A. Bodin, P. Gatenholm, Mechanism of assembly of xylan onto cellulose surfaces, Langmuir 19 (2003) 5072. [6] A. Escalante, A. Gonçalves, A. Bodin, A. Stepan, C. Sandström, G. Toriz, P. Gatenholm, Flexible oxygen barrier films from spruce xylan, Carbohydrate Polymers 87 (2012) 2381. [7] L.S. McKee, H. Sunner, G.E. Anasontzis, G. Toriz, P. Gatenholm, V. Bulone, F. Vilaplana, L. Olsson, A GH115 α-glucuronidase from Schizophyllum commune contributes to the synergistic enzymatic deconstruction of softwood glucuronoarabinoxylan, Biotechnology for Biofuels 9 (2016) 2. [8] G. Golan, D. Shallom, A. Teplitsky, G. Zaide, S. Shulami, T. Baasov, V. Stojanoff, A. Thompson, Y. Shoham, G. Shoham, Crystal structures of Geobacillus stearothermophilus α-glucuronidase complexed with its substrate and products MECHANISTIC IMPLICATIONS, Journal of Biological Chemistry 279 (2004) 3014. [9] D. Nurizzo, T. Nagy, H.J. Gilbert, G.J. Davies, The structural basis for catalysis and specificity of the Pseudomonas cellulosa α-glucuronidase, GlcA67A, Structure 10 (2002) 547. [10] P.M. Martínez, M.M. Appeldoorn, H. Gruppen, M.A. Kabel, The two Rasamsonia emersonii α-glucuronidases, ReGH67 and ReGH115, show a different mode-of-action towards glucuronoxylan and glucuronoxylo-oligosaccharides, Biotechnology for Biofuels 9 (2016). [11] B. Cobucci-Ponzano, A. Strazzulli, R. Iacono, G. Masturzo, R. Giglio, M. Rossi, M. Moracci, Novel thermophilic hemicellulases for the conversion of lignocellulose for second generation biorefineries, Elsevier 78 (2015) 63. [12] J. Sambrook, D.W. Russell, Molecular Cloning: A Laboratory Manual, CSHL Press, 2001. [13] U.K. Laemmli, Cleavage of structural proteins during the assembly of the head of bacteriophage T4, Nature 227 (1970) 680. [14] A. Rogowski, A. Baslé, C.S. Farinas, A. Solovyova, J.C. Mortimer, P. Dupree, H.J. Gilbert, D.N. Bolam, Evidence that GH115 α-glucuronidase activity, which is required to degrade plant biomass, is dependent on conformational flexibility, The Journal of Biological Chemistry 289 (2014) 53.